Effective power analysis of multi‐tone excitation transmitting system. Issue 21 (18th October 2019) - Wei, Maogang; Yang, Furong; Huang, Haiyan; Shan, Kun
Abstract : Inter‐modulation would occur when the transmitting system is under multi‐tone excitation; therefore, the non‐linear response of power amplifier unit should be considered in the system design. Here, by establishing non‐linear theory simulation model of the transmitting system, we introduce the channel consistency factor, put forward the concept of effective jamming power, analyse the effective power of the multi‐channel array transmitting system under multi‐tone excitation, and carry out relevant experiments for verification, thereby providing reference for the design of multi‐signal transmitting system.